Angular dependence of g-shifts of Kramer's doublets in a crystal under uniaxial stress. - Calvo, Rafael; Fainstein, C.; Oseroff, S. B.; Terrile, M. C (1969)
Fil: Calvo, Rafael Comisión Nacional de Energía Atómica; Argentina